Konsep Sosialisme Islam menurut Sayid Quthb - Asnawiyah Asnawiyah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
This paper attempts to trace how the concept of social thinking introduced  by Sayyid Qutb, better known by the concept of Islamic socialism. Socialism is  one of the tenets that wants the Elimination of social inequalities in society. This  teaching is done in an effort to bridge between the luxury life with the life of the  lower classes, so that gave birth to life balance in a public order. Observing this,  then social systems analyze three important aspects, namely: first, the public  relations of various systems; Secondly, the normal situation or a situation of  balance, in line with normal conditions, and third, all systems perform normal  system to reintegration. Thought Sayid Qutb give new shades of thought in the  aspect of community development in Islam. He sought to correlate to the thinking  that is introduced by the West and the Islamic version of the social aspect of  teaching.